2021
DOI: 10.1542/hpeds.2020-001719
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 in Pediatrics: Characteristics of Hospitalized Children in New Jersey

Abstract: OBJECTIVES: Understanding the risk factors, predictors, and clinical presentation of coronavirus disease 2019 (COVID-19) in pediatric patients with severe disease. METHODS: We conducted a retrospective chart review of pediatric patients admitted between March 1, 2020, and May 31, 2020, to a large health network in New Jersey with positive test results for severe acute respiratory syndrome coronavirus 2 on reverse transcriptas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 13 publications
0
13
0
Order By: Relevance
“…We found similar trends in socioeconomic status and ethnicity to previously published studies. 19,20 Specifically, even accounting for a high percentage of admissions of Hispanic, Spanish-speaking, and publicly insured children during the same time period, these populations were substantially overrepresented in our SARS-CoV-2 patients (86% vs 66.2% Hispanic, 34% vs 17.8% Spanish-speaking, and 88% vs 74.8% publicly insured or uninsured). Current available data reveal that vaccination rates among Hispanic/Latinx individuals lag substantially behind non-Hispanic white individuals, despite this population being heavily represented in essential industries.…”
Section: Discussionmentioning
confidence: 89%
“…We found similar trends in socioeconomic status and ethnicity to previously published studies. 19,20 Specifically, even accounting for a high percentage of admissions of Hispanic, Spanish-speaking, and publicly insured children during the same time period, these populations were substantially overrepresented in our SARS-CoV-2 patients (86% vs 66.2% Hispanic, 34% vs 17.8% Spanish-speaking, and 88% vs 74.8% publicly insured or uninsured). Current available data reveal that vaccination rates among Hispanic/Latinx individuals lag substantially behind non-Hispanic white individuals, despite this population being heavily represented in essential industries.…”
Section: Discussionmentioning
confidence: 89%
“…We identified 9937 potentially relevant records from the literature databases and registers, and 1575 records from the additional searches. After screening the titles, abstracts and full texts, 56 studies (22 cohort studies, 9 case-control studies, and 25 case series) with a total of 79,104 patients were included [ [10] , [11] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] , [67] , [68] , [69] , [70] , [71] , [72] , [73] , [74] , [75] , [76] ] ( Fig. 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…A total of 24 studies assessed factors associated with the risk of admission to ICU [ 10 , 11 , [24] , [25] , [26] , [27] , [28] , [29] , [31] , [32] , [33] , [34] , [35] , 41 , 43 , 44 , 54 , 57 , 58 , [61] , [62] , [63] , [64] , 70 ]. The pooled results from three studies showed that age less than 1 month was associated with an increased risk of admission to ICU ( OR =2.29, 95% CI 1.48 to 3.56, moderate-quality evidence).…”
Section: Resultsmentioning
confidence: 99%
“…Children with serious illnesses represent a small percentage of the pediatric population yet they may be particularly vulnerable to adverse outcomes due to underlying conditions and treatments such as immunosuppressive therapy. 17 , 18 , 19 Routine challenges parent caregivers of seriously ill children face may also be compounded by additional considerations such as complex care coordination, 20 high reliance on hospital-based services and medical technology, 17 worries related to the child's enhanced vulnerabilities 22 and maintaining routine care such as disease directed therapies, school-based therapies, and home nursing for activities of daily living support. 14 , 15 , 23 In addition, certain hospital-based or rehabilitation services cannot feasibly occur at home or through telehealth.…”
Section: Introductionmentioning
confidence: 99%